TEORI KEPERAWATAN MERLE H MISHEL - Wicke Afriza; Irna Nursanti (Nusantara Hasana Journal, 2024)
Merle H. Mishel was born in Boston, Massachusetts. Dial graduated from the University of Boston with a B.A. in 1961 and earned an M.S. in psychiatric nursing from the University of California in 1966. Mishel completed her M.A. and Ph.D. D in the area of ​​social psychology at the Claremont Graduate School in Claremont, California in 1976 and 1980. The dissertation research was supported by a Nation Research Service Award to develop and test the Perceived Ambiguity in Illness Scale measuring instrument, which is now known as the Mishel Uncertainly in Illness Scale (MUIS-A). One of the experts in nursing is Merle H. Mishel who has the Middle Range theory with his theory of uncertainty. This theory states that the meaning associated with the situation of illness, occurs when decision makers are unable to carry out their duties and interpret objectively, or the inability to accurately predict the expected outcome (Mishel, 1998. Nursing as a profession is unique because nursing addresses a variety of individual responses , family and community regarding the health problems they face. Nurses have various roles such as care givers, primary nurses, clinical decision makers, advocates, researchers and educators. Nurses often have to carry out more than one role at the same time, so that in carrying out their duties They must have the same frame of mind. It is necessary to believe that the application of quality nursing theory in the implementation of nursing care will have an impact on improving the quality of nursing care. Nursing services as professional services will develop if they are supported by nursing theories and models as well as the development of nursing research and implemented in practice. nursing.